Fanconi Syndrome Secondary to Deferasirox in Diamond–Blackfan Anemia: Case Series and Recommendations for Early Diagnosis. Issue 8 (15th April 2016) - Papneja, Koyelle; Bhatt, Mihir D.; Kirby‐Allen, Melanie; Arora, Steven; Wiernikowski, John T.; Athale, Uma H.
Abstract : Deferasirox is an oral iron chelator used to treat patients with transfusion‐related iron overload. We report, from two institutions, two children with Diamond–Blackfan anemia who developed Fanconi syndrome secondary to deferasirox administration, along with a review of the literature. The current recommendation for the laboratory monitoring of patients receiving deferasirox does not include serum electrolytes or urine analysis. Thus, despite routine clinic visits and bloodwork, these two patients presented with life‐threatening electrolyte abnormalities requiring hospitalization. Hence, we propose the inclusion of serum electrolytes and urine analysis as part of routine monitoring to facilitate the early diagnosis of Fanconi syndrome in the context of high doses of deferasirox therapy.